Konferentsiia demokraticheskikh organizatsii SSSR . Konferentsiia demokraticheskikh organizatsii SSSR . Conference of Soviet Democratic Organizations . Конференция демократических организаций СССР - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Discussion of democratic organizations of the USSR and Europe. Featured in the program: Luk'ianenko, Levko (Head of the Ukrainian Republican Party) Обсуждение демократических организаций СССР и Европы. В программе участвуют: Лукьяненко, Левко (Глава Украинской республиканской партии)